1997
DOI: 10.1137/s1052623495283024
|View full text |Cite
|
Sign up to set email alerts
|

Global Continuation for Distance Geometry Problems

Abstract: Distance geometry problems arise in the interpretation of NMR data and in the determination of protein structure. We formulate the distance geometry problem as a global minimization problem with special structure, and show that global smoothing techniques and a continuation approach for global optimization can be used to determine solutions of distance geometry problems with a nearly 100% probability of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(98 citation statements)
references
References 15 publications
0
98
0
Order By: Relevance
“…Also, when the problem is specified by the upper and lower bounds, we have numerically demonstrated that quite accurate configurations are generated when n is up to 300. It should be emphasized that the existing algorithms such as [7,10,18,25,19] need to iterate the search procedures from a large number of starting points, while our algorithm generates accurate configurations without those iterations, which would be the advantage of our algorithm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, when the problem is specified by the upper and lower bounds, we have numerically demonstrated that quite accurate configurations are generated when n is up to 300. It should be emphasized that the existing algorithms such as [7,10,18,25,19] need to iterate the search procedures from a large number of starting points, while our algorithm generates accurate configurations without those iterations, which would be the advantage of our algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these results indicate that the number of specified pairs ISI does not affect the quality of the configurations. Compared to the results in [10,18,25], our algorithm generates acceptable configurations even when the number of the specified pairwise distances, ISI, are small, which enables us to solve the larger size problems with up to 729 points. Figure 2 and Figure 3 show the typical behavior of the algorithm.…”
Section: Ij )Es Sidmentioning
confidence: 93%
See 2 more Smart Citations
“…Molecular structure generating algorithms incorporating distance geometry techniques have continued to be published since originally championed by Crippen and Havel; [7][8][9][10][11][12][13] Of particular interest is Crippen's linearized embedding approach. 7 In Crippen's algorithm, 7 a molecule to be embedded in Euclidean 3-space is represented by a spanning tree rooted at the most central atom.…”
Section: Introductionmentioning
confidence: 99%